2020
DOI: 10.1038/s41598-020-60106-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating physicochemical properties of crude oil as indicators of low-salinity–induced wettability alteration in carbonate minerals

Abstract: the injection of low-salinity brine enhances oil recovery by altering the mineral wettability in carbonate reservoirs. However, the reported effectiveness of low-salinity water varies significantly in the literature, and the underlying mechanism of wettability alteration is controversial. In this work, we investigate the relationships between characteristics of crude oils and the oils' response to low-salinity water in a spontaneous imbibition test, aiming (1) to identify suitable indicators of the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Many inconsistencies are then obtained when comparing the two methods. According to other studies, the oil/water interface generally exhibits a more negative value than the rock/water interface, especially in low salinity conditions [15,42,59,63,64], which is in agreement with our results using EPM.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Many inconsistencies are then obtained when comparing the two methods. According to other studies, the oil/water interface generally exhibits a more negative value than the rock/water interface, especially in low salinity conditions [15,42,59,63,64], which is in agreement with our results using EPM.…”
Section: Methodssupporting
confidence: 93%
“…Also, they observed one specific case where it was not possible to correctly predict the response, which questions a possible causal relationship between electrostatic repulsion and additional oil recovery. An absence of clear correlation has also been observed by other authors [42,43]. Hence, interpretation must be done case by case to determine the efficiency of CSW on the COBR system under consideration.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Carbonate reservoirs contain a substantial amount of the world’s oil reserves 1 , but unfortunately, their recoveries are not as high as enough 2 . Laboratory experiments and field trials have shown that enhanced oil recovery from carbonate reservoirs can be obtained by modifying the injected brine composition in a process called low-salinity water flooding (LSWF) 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Details of group density, monomeric vs. polymeric, or structure, short vs. long chains, are concealed in these numbers. Correlating the magnitudes of both numbers with wettability has been investigated for a long time, e.g., Dubey and Doe (1993); Farooq et al 2019; Song et al (2020). Some researchers have tried to vary the values of both numbers or the ratio between the numbers to be correlated with recovery (Puntervold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%